CORE COMPETENCES OF PIRACY AND MARITIME TERRORISM - Piotr Gawliczek (Journal of Defense Resources Management, 2016)
The intensity of the attacks, the level of violence, the scale of destruction in the maritime areas forces creation of certain security conditions. Recognizing the enemy - piracy and maritime terrorism - by identifying their resources, skills and competences is necessary action in building the safety of vessels and maritime infrastructure. Building competence of terrorist organization and maritime piracy requires the involvement of many interrelated resources and their proper coordination. It seems that, as in a business model, in these criminal organizations there are similar resources, skills and competences that determine the advantage and strategic value of the organization. However, the weight of each factor is different. The same assumption can be related to piracy and the activities of the terrorist organization at sea. The results of the study suggest that the main sources of success of analyzed criminal organizations generate harm for national security. In the case of piracy, they result from the following spheres: human capital, attributable to the skills capital; structural capital, belonging to innovation capital; relational capital, depending on customers' capital. As for terrorist activities, they stem from the spheres of: human capital, belonging to social capital; structural capital, attributable to the process capital; relational capital and determined by capital of standing out. In summary, this article is intended to show a terrorist organization and maritime piracy through the prism of resources theory, skills and competences of strategic management. As one of the first, it places many questions, formulate some theses in the area of competences of organizations. Answering the questions, verification of posed theses, requires also in-depth research that will be published in subsequent works.